2010
DOI: 10.1093/molbev/msq174
|View full text |Cite
|
Sign up to set email alerts
|

Demosponge EST Sequencing Reveals a Complex Genetic Toolkit of the Simplest Metazoans

Abstract: Sponges (Porifera) are among the simplest living and the earliest branching metazoans. They hold a pivotal role for studying genome evolution of the entire metazoan branch, both as an outgroup to Eumetazoa and as the closest branching phylum to the common ancestor of all multicellular animals (Urmetazoa). In order to assess the transcription inventory of sponges, we sequenced expressed sequence tag libraries of two demosponge species, Suberites domuncula and Lubomirskia baicalensis, and systematically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…They have no true tissues and organs and lead a sessile lifestyle. Due to the fact that they have changed little during evolution, they probably provide the best insight into the metazoan ancestors' genomic features (Cetkovic et al 2004;Perina et al 2006;Cetkovic et al 2007;Philippe et al 2009;Harcet et al 2010;Srivastava et al 2010). Real number of the Nme proteins in sponge Suberites domuncula is possibly higher than we previously reported because EST database used in S. domuncula Nme study (Harcet et al 2005) contained at most 4500 non-redundant cDNA sequences, which is certainly far less than the total number of genes in the S. domuncula genome.…”
Section: Introductionmentioning
confidence: 71%
“…They have no true tissues and organs and lead a sessile lifestyle. Due to the fact that they have changed little during evolution, they probably provide the best insight into the metazoan ancestors' genomic features (Cetkovic et al 2004;Perina et al 2006;Cetkovic et al 2007;Philippe et al 2009;Harcet et al 2010;Srivastava et al 2010). Real number of the Nme proteins in sponge Suberites domuncula is possibly higher than we previously reported because EST database used in S. domuncula Nme study (Harcet et al 2005) contained at most 4500 non-redundant cDNA sequences, which is certainly far less than the total number of genes in the S. domuncula genome.…”
Section: Introductionmentioning
confidence: 71%
“…Rapid genomic and intronic expansion was most likely the driving force behind the radiation of the eumetazoan lineage (Putnam et al 2007; Harcet et al 2010; Srivastava et al 2010), playing out at an intermediate evolutionary depth. In multiple plant species, whole genome duplications have been associated with drastic changes in the environment (Blanc and Wolfe 2004; Van de Peer et al 2009), potentially enabling these species to survive.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic analysis of the sponge gene repertoire showed that the genomic complexity was already present at the very beginning of metazoan evolution, before the appearance of tissue or any other complex morphological feature found in extant animals. 10 Previous analyses of phylogenetically conserved genes/proteins in sponges identified a number of very sophisticated multifunctional enzymes whose functions are usually associated with human diseases. 3,11,12 Btk-like 700-aa-long protein from the marine sponge Suberites domuncula (Demospongia) was described previously.…”
Section: Introductionmentioning
confidence: 99%